Khitan Perempuan dalam Sunan Abu Daud - Romziana, Luthviyah; Zaiyadi, Ahmad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2020)
The word khitan (circumsion) come from the word khatn, wich mean that the part that is cut from the boys or the girls genetalia. Khitan from prophet Ibrahim in the past also get circumcision althought his age is 80 years old. Khitan (circumsion) for girl known by the term female genital cutting and female circumsion. Practically, female genital is done by cutting of all clitoris then saw it until remain a little hole. Where this practice model is used many times at the Pharaoh's time in ancient Egypt as an effort oppression of women and decrease sexual libido. In this case, circumsion for girl will be explained at hadits that was narated by Abu Dawud. Keyword: Khitan, female genitale mutilation, Sunan Abu Dawud